Type 2 Diabetes Mellitus Increases the Risk to Hip Fracture in Postmenopausal Osteoporosis by Deteriorating the Trabecular Bone Microarchitecture and Bone Mass - Sahar Mohsin; Suneesh Kaimala; Jens Jolly Sunny; Ernest Adeghate; Eric Mensah Brown (Journal of Diabetes Research)
T2DM is linked to an increase in the fracture rate as compared to the nondiabetic population even with normal or raised bone mineral density (BMD). Hence, bone quality plays an important role in the pathogenesis of skeletal fragility due to T2DM. This study analyzed the changes in the trabecular bone microstructure due to T2DM at various time points in ovariectomized and nonovariectomized rats. Animals were divided into four groups: (I) control (sham), (II) diabetic (sham), (III) ovariectomized, and (IV) ovariectomized with diabetes. The trabecular microarchitecture of the femoral head was characterized using a micro-CT. The differences between the groups were analyzed at 8, 10, and 14 weeks of the onset of T2DM using a two-way analysis of variance and by post hoc multiple comparisons. The diabetic group with and without ovariectomies demonstrated a significant increase in trabecular separation and a decrease in bone volume fraction, trabecular number, and thickness. BMD decreased in ovariectomized diabetic animals at 14 weeks of the onset of T2DM. No significant change was found in connectivity density and degree of anisotropy among groups. The structural model index suggested a change towards a weaker rod-like microstructure in diabetic animals. The data obtained suggested that T2DM affects the trabecular structure within a rat’s femoral heads negatively and changes are most significant at a longer duration of T2DM, increasing the risk to hip fractures.